GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 120882366 species occurrences available in GBIF matching the query: TaxonKey: Magnoliophyta Cronquist, Takhtajan & W. Zimmermann, 1966 or Pinophyta HasCoordinate: true HasGeospatialIssue: false. The dataset includes 120882366 records from 2114 constituent datasets: 1 records from Glemstal (Leonberg). 75 records from LK 11 im Mönchspark. 23 records from Lahnufer in Villmar. 79340 records from Jordal. 89 records from Zielbach (Töll). 41 records from Hettstadt Gehäge. 1879 records from ANTARCTIC PLANT DATABASE. 25 records from GEO-Tag am Hohlen Stein. 2 records from 2. Donauinsel bei Entau. 24 records from Sponges of Rathlin Island. 331581 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 206575 records from R. L. McGregor Herbarium Vascular Plants Collection. 1024670 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 32 records from Gym Freyung. 64 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 13 records from FND "Weißer Berg" Leißling. 3 records from Wiese. 31670 records from Plant Specimens of Kurashiki Museum of Natural History. 66042 records from United States National Plant Germplasm System Collection. 9421 records from The Orchid Atlas of Western Australia. 526 records from National Trust - Heigham Holmes species data held by The National Trust. 61 records from Wassermann. 14 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 26 records from Umgebung des Spalatin Gymnasium Altenburg. 29 records from Fürstenberger Ralley Teil 3. 59 records from VFD-HH/SH: Pferdweide Lammert. 9316 records from MEXU/Plantas Vasculares. 1082 records from MEXU/Tipos de plantas vasculares. 79628 records from Vascular Plants, Observations, Oslo (O). 165 records from Kernberge und Umgebung (Jena). 25 records from Klimaoasen in Köln. 10 records from An der Ohm, (Wettsaasen). 6 records from Foraminifera abundance of Hole 17-167. 110318 records from The digitization of plant specimens of NTU. 255 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 74 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 160 records from Mooswald (Freiburg). 1305 records from Flora genérica de las gramíneas del estado de Tlaxcala. 5025 records from The Erysiphales Collection at the Botanische Staatssammlung München. 28 records from Freiheitsring (Frechen). 34560 records from Kathryn Kalmbach Herbarium. 83152 records from BioGIS - Vascular plants - INPA database. 76 records from Wirbach-Taubental (Bad Blankenburg). 144 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 46 records from Südwestlich der Parkwiesen. 95 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 81 records from Donauinsel des BN bei Entau. 21 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 1554 records from Biodiversidad de Datura (Solanaceae) en México. 38 records from Flora und Fauna in unserer Kita. 85 records from Selztal bei Friesenheim. 239 records from Zukünftiges NSG Höftland/Bockholmwik. 23115 records from svalbardflora.net. 266001 records from Observational database of Icelandic plants. 1785 records from Eppingen und Umgebung. 21 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 119549 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 16 records from Zwickau- Schwanenteich. 4 records from Tuttlinger Tag der Artenvielfalt. 234 records from Naturschutzgebiet Sistig-Krekeler-Heide. 19 records from Motzener Tonsee. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 31 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 95 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 61 records from Plant specimens of Hokkaido University Museum. 1 records from Foraminifera abundance of Hole 55-432A. 1534651 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 30696 records from MEXU/Asteraceae. 132 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 4 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 1313 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 532 records from Monitoring data from the federal state Hesse (Germany). 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 1093 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 588 records from NHT flora. 3 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 65 records from Düne am Ulvenberg (Darmstadt). 51800 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 14350 records from ArtenFinder. 42 records from Wiese am Unterbecken. 2 records from Ökosysteme rund um Wedel. 20527 records from Herbarium de Geo. B. Hinton, México. 137 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 378 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 127535 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 583 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 4 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 7618 records from CRI - Herbário Pe. Dr. Raulino Reitz. 54010 records from Irish Vascular Plant Data - Paul Green. 4 records from Schulwald Regionale Schule Sprendlingen. 5204 records from Nordic Genetic Resources. 3154 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 88 records from LauWi. 30 records from Wahner Heide LK 12 Biologie. 1680 records from KTU Pinophyta. 2395 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 22 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 8854 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 13127 records from Impetus - Herbarium Hamburgense. 56 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 66 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 70 records from Schulhof und Anlagensee in Nellingen. 5824 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 11239 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 39 records from Parcela Permanente en el Pantano Martos. 68 records from Artenvielfalt auf dem Schulgelände. 9561 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 77 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 2696 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 22 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 33 records from Heidesee / Halle. 37 records from Streuobstwiesengelände St.Meinrad Gymnasium. 19 records from Ibaraki Nature Museum, Algae collection. 986 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 1278 records from Local BioBlitz Challenge 2013. 21528 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 19 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 28 records from Chrysomelidae of Poland. 1 records from Kirchenforst. 3727 records from Mountain Invasion Research Network (MIREN) survey. 48 records from Schulhof Bühlschule Giengen. 47867 records from Bernice P. Bishop Museum. 35 records from Parkuntersuchung Weißer See. 40 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 10 records from Lichens of Knyszyn Forest. 1 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 27 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 140 records from privater Garten. 80 records from BioMar - LIFE project. 4 records from Streuobstwiese (Mittelgasse 4). 121 records from Binsenwiesen. 28 records from Garten in Schmölln. 10 records from Landschaftsschutzgebiet Buchhorst2. 4 records from Arizona State University Lichen Collection. 36062 records from Herbarium (UNA). 52 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 90 records from Invertebrates Collection of the Swedish Museum of Natural History. 4167 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 160 records from 3. Tag der Artenvielfalt Hockenheim. 8505 records from UPCB - Herbário do Departamento de Botânica. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 81 records from Tiere und Pflanzen am Pfannenbach. 48877 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 3999 records from Sightings Map of Invasive Plants in Portugal. 2958 records from Millenium Seedbank (MSB). 848 records from NINA Vanndata øvrige arter. 20662 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 140 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 28373 records from Phanerogamic Botanical Collections (S). 590293 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 26 records from Feuchtbiotop Weidenkaule. 129 records from Unser Schulhof - eine Apotheke. 35 records from Trockenrasen bei Dörndorf. 14 records from Schulgelände Ceciliengymnasium. 3 records from Schulhof Montessori Schule (Rotenburg / Wümme). 111 records from Stadtpark Sulzbach-Rosenberg. 59 records from Weidenhüttendorf an der Würm (München). 167866 records from The Flora of County Waterford. 48 records from Fliegenhaupt Marksuhl. 7 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 163 records from Biotope in Rheine - Aktion 350. 7 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 69 records from Klütwald. 179 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 3245 records from National Trust - Ickworth species data held by The National Trust.. 153 records from DJH. 7 records from Leben auf einer Sturmfläche. 115 records from WildesMoor bei Schwabstedt. 37 records from Landschaftspark St.Leonhard-Deisendorf. 28516 records from JPB - Herbário Lauro Pires Xavier. 9479 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 3 records from Grünanlagen Stadt Brandenburg an der Havel. 28 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 111 records from Flora. 106 records from Obstwiese Osterberg. 375 records from Bulau. 758 records from Flora útil del Municipio de la Huerta, Jalisco. 22 records from Relative abundance of deep-sea benthic foraminifera in surface sediments east of New Zealand. 45 records from Rund ums Ökohaus (Würzburg). 292 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 1 records from University of Florida Vertebrate Paleontology. 429 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 506 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 8142 records from Flora of Słowiński National Park, Poland. 9 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 8 records from Schulgarten Janusz-Korczak-Realschule. 316715 records from BSBI tetrad data for Ireland. 1 records from Benthic foraminifera abundance of Hole 42-372. 47 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 423 records from EAN - Herbário Jaime Coelho de Moraes. 114 records from NABU-Auerochsenweide. 2797 records from Individual Sightings. 282 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 11925 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 7434 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 7866 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 18362 records from Endemic plants of the Congo basin. 261 records from Schatzinsel Wangerooge. 29 records from Schüler erforschen die Helme-Aue. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 3 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 94 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 1708 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 3 records from UWBM Herpetology Collection (Arctos). 38 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 136437 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 7 records from MfN - Fossil invertebrates Ia. 84 records from Bergbaufolgelandschaft am Muldestausee. 9848 records from Herbarium of Umeå University (UME). 615 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 492895 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 72 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 43 records from Tongrube bei Hettstedt. 13 records from Wasser-Lernort Nettemündung. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 1511 records from The French Collection of Medicago truncatula. 68165 records from Biologiezentrum Linz. 175 records from Naturgarten Langenholtensen. 15 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 36409 records from Irish vascular plant data 1999-2009. 1 records from KU Museum of Invertebrate Paleontology. 44252 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 41 records from Schulgelände Thurmair-Gymnasium. 84 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 1358 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 143 records from Naturerlebnisraum Koppelsberg. 937 records from National Trust - Sutton Hoo species data held by The National Trust.. 20304 records from Staffordshire Ecological Record - SER Species-based Surveys. 82252 records from UCJEPS TAPIR Provider. 118 records from Föhrenried (Fronreute und Baindt). 12 records from Altholzparzelle Eilenriede Hannover. 150524 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 19 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 660 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 27 records from Estetal (Buxtehude). 157599 records from UA Herbarium. 193 records from IBF Monitoring of Lichens. 1 records from Benthic foraminifera abundance of Hole 84-566C. 63342 records from Royal Botanic Garden Edinburgh Herbarium (E). 91 records from Vielfalt verschiedener Wiesen. 195 records from Schulgarten der Volksschule. 9 records from Steinbruch Mainz-Weisenau, 4.Jahr. 278 records from GEO-Hauptveranstaltung (Insel Vilm). 18 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 576 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 11 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 1 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 4232 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 1640 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 41 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 135 records from Artenvielfalt im Rhein-Neckar-Raum. 1093 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 868 records from Kartlegging av spredning av fremmede bartrær. 169 records from Philosophenwald und Wieseckaue in Gießen. 69 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 67 records from Tiergarten (Zeitz). 24 records from Koleopterologen am Bausenberg. 3933 records from Census of plant species in Pahou forest reserve. 27 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 1 records from Vogelwelt im Europa-Rosarium. 1 records from Chrysomelidae of the Carpathians. 18925 records from Herbario de la Universidad de Arizona, EUA. 157917 records from Geneva Herbarium – General Collection (G). 25 records from Lassentiner Moor (Niepars). 1603 records from MEXU/Flora de Oaxaca. 1 records from Regenwasserabfangsbecken (Erlenbach). 2608 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 249 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 353 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 154216 records from The Himalayan Uplands Plant database (HUP Version 1). 87 records from Artenbestimmung. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 52 records from Waldi-Weiher. 12 records from Landwehrbach. 33 records from Lüner Holz (Lüneburg). 43 records from Schafsweide Seniorenhaus Berghof. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 50 records from Mönchspark. 7634 records from Institut Botanic de Barcelona, BC-Histórico. 94 records from Arteninventar rund um den Rannahof. 476 records from Natural History Museum, University of Tartu. 98 records from Steinbruch Mainz-Weisenau, 2. Jahr. 26 records from Schulgarten Fichteschule. 52 records from Biotope im Schulumfeld. 4341 records from National Trust - Hatfield Forest species data held by The National Trust.. 68 records from Sahrbachtal Kreis Ahrweiler. 3468 records from Polish seed gene bank – historical passport data of accessions. 212 records from Bayerische Donau - Leipheim. 725 records from Faun. 1644 records from JOI - Herbário Joinvillea. 27 records from NOAA HML Tidal Creek Database. 212 records from Colección nacional de palmas de Colombia - JBQ. 112 records from Bodenteicher Seewiesen. 2396 records from Universität Salzburg. 447 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 3220 records from SANT herbarium vascular plants collection. 182 records from Luderbusch. 10 records from Bayerische Donau - Riedlingen. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 26 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 186 records from Wangerooge. 61 records from BB-Biodiversität b. 125 records from Bayerische Donau - Neu Ulm. 35 records from MedOBIS (EurOBIS). 248 records from Stadtgebiet (Dannenberg). 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 46 records from Grenzturm Hohen Neuendorf. 96 records from Paul-Gerhardt-Schule Dassel. 22 records from Tiere und Pflanzen um uns herum !. 199 records from Kühmark bei Wetzlar. 2 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 14 records from Weevils of Wales and England. 5988 records from HRCB - Herbário Rioclarense. 9 records from Alien Species in Poland - Animals. 13 records from Bayerische Donau - Tapfheim. 13 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 27 records from Schulhof A.-Lindgren-Schule (Elmshorn). 27 records from Schulteich Freie Waldorfschule Darmstadt. 48535 records from Flora d'Andorra. 41 records from Umgebung von Schorndorf. 173 records from Wupperaue bei Kemna (Wuppertal). 10335 records from UFP - Herbário UFP - Geraldo Mariz. 74 records from Landschaftsschutzgebiet "Holmer Sandberge". 1 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 2 records from Zwischen Enz und Schule. 2626 records from Recuento de la diversidad florística de Veracruz. 188 records from Fuldaaue (Stadtgebiet Fulda). 3625 records from ARKO strandeng. 71 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 1966 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 1384 records from Herbarium Rhoenmuseum Fladungen. 6 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 19 records from Nottekanal, Klasse 7 - 10. 28 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 211115 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 53 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 3820 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 2 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 74 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 6 records from Highland Biological Recording Group - HBRG Insects Dataset. 5 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 39 records from Zitadelle Berlin-Spandau (7b). 29 records from Rotes Steigle (Panzerübungplatz Böblingen). 5 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 30 records from Kindervilla Aussengelände/ Hiltroper Park. 3163 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 5900 records from Vascular Plants Collection of Sagamihara City Museum. 3148 records from Herbier A. Le Grand (BOUM). 1426 records from The Erysiphales Collection at the University Halle-Wittenberg. 33 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 161 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 5489 records from National Invasive Species Database. 7 records from 2. Aspacher GEO-Tag der Artenvielfalt. 34 records from Flora und Fauna im Brexbachtal. 822 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 9524 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 4950 records from Natural History Museum Maastricht (NL) - Herbarium. 1 records from FTEA. 114 records from Grünes Germersheim. 90 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 39 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 3257 records from fundiv france database. 806471 records from Naturalis Biodiversity Center (NL) - Botany. 3712 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 50 records from (Appendix Table 2) Absolute abundances of benthic foraminifers in DSDP Site 94-610. 318 records from Bayerische Donau - Blindheim Donaubrücke. 7 records from (Table 1) Neogene benthic foraminifers of ODP Hole 120-747A. 1553 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 4016837 records from Australia's Virtual Herbarium. 72 records from Regionalpark(Hattersheim). 83559 records from CAS Botany (BOT). 33 records from Schulhofuntersuchung Thomas-Mann-OS. 3 records from Amphibian observations from Nida Valley. 48 records from Streuobstwiese Stedar. 56 records from Schloß Türnich (Kerpen). 48 records from Streuobstwiese Stedar 2008. 6923 records from Lista florística preliminar de Tamaulipas. 39 records from Teich Berlin Wuhlheide. 120 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 77 records from Schiller Gymnasium Hof 10b. 1 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 1 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 67 records from Sukzession Industriebrache. 4149 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 3539 records from TEPB - Herbário Graziela Barroso. 9396 records from University of British Columbia Botanical Garden Collections (UBCBG). 29 records from (Table 22) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-594. 71 records from Spießwoogtal / Königsbruch (Fischbach). 32 records from LSG "Großes Bruch". 3809 records from Universitat de Girona: HGI-Cormophyta. 982195 records from Belgian IFBL Flora Checklists (1939-1971). 100 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 360 records from Revisión taxonómica del género Furcraea (Agavaceae) en México y Guatemala. 91 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 14 records from AKG-Bensheim. 8286714 records from Botanical Society of the British Isles - Vascular Plants Database. 45388 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 288 records from LaBoOb02. 31 records from Rosarium (LMS), Klasse 6a. 1 records from MSB Parasite Collection (Arctos). 3 records from AWI-Herbarium Marine Macroalgae. 146 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 85 records from Grillhütte Wettsaasen, Wiese, Hecken. 13 records from Herbarium of The New York Botanical Garden. 49 records from Dalbek-Schlucht. 282 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 198330 records from Israel Nature and Parks Authority. 3 records from Benthic foraminifera abundance of Hole 84-566. 4 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 294 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 49 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 33 records from Flusswerder in der Weser (Hameln). 87 records from VFD-RP: Taunus: Kirchenweide Köpplers. 22 records from Liether Park 1 (LMS), Klasse 5b. 160 records from Langes Tannen (Uetersen). 4 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 2392 records from Census of plant species in Bonou forest reserve (Southern Benin). 57 records from Müritz-Nationalpark. 148 records from Schlattstaller Tal (Lenningen). 1 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 1364 records from Monitoring data from the federal state Bavaria (Germany). 40 records from Biodiversidad de Veracruz: Oligochaeta. Annelida. 94 records from Naturschutzgebiet Müchelholz (Mücheln). 20339 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 69 records from Danisco-Wiese. 13 records from Dellwiger Bach (Dortmund). 190 records from Tag der Artenvielfalt in Heidelberg. 3139 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 39546 records from Programa de repatriación de datos de ejemplares mexicanos. 146 records from Umgebung der Gesamtschule Winterhude (Hamburg). 339874 records from Données ONF Faune-Flore-FOnge. 96 records from Ehmkendorf. 2088 records from Estudio florístico de las gramíneas de Zacatecas. 294 records from Biologische Station im Kreis Wesel. 105 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 85 records from Aachtobel. 167 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 11 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 34541 records from Occurrences in SinBIOTA. 16 records from Carabidae of Poland. 790 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 30 records from Artensuche auf den Elbwiesen in Radebeul. 5 records from Landesgartenschau. 131 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 2629 records from HST - Herbário Sérgio Tavares. 7 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 58 records from Herbario de la Universidad de Granada: GDA. 31959 records from West African Vegetation Database. 1469 records from The Lichen Collection at the Botanische Staatssammlung München. 2672 records from Estudio biosistemático del género Bouteloua (Poaceae) en México. 33874 records from Gunma Museum of Natural History, Vascular Plant Specimen. 10 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 46 records from Dörnberg. 81 records from Werl macht sich auf die Suche. 24616 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 4603 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 19 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 32 records from GE-Brühl. 19 records from Chrysomelidae of Central Europe. 296325 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 3630517 records from FlorKart - FlorenKartierung Gefaesspflanzen. 24 records from Reusaer Wald. 32 records from Harold W. Manter Laboratory of Parasitology Collection. 1 records from Michigan State University Herbarium Lichens. 52822 records from Botany Division, Yale Peabody Museum. 2335 records from La etnobiología de los recursos nutritivos en las comunidades Tzeltales en los Altos de Chiapas. 241582 records from Staffordshire Ecological Record - SER Site-based Surveys. 90040 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 1 records from British Lichen Society - BLS Lichen Database: Wales. 250 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 84 records from Stever. 37 records from Schulgarten-St.-Georg-Gymnasium. 417 records from BÜG. 35 records from Waldhusener Moor (Lübeck-Kücknitz). 98 records from Bizzenbachtal (Wehrheim/Taunus). 11 records from Bilder der Natur. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 563010 records from FLORIVON. 41 records from Artenvielfalt auf der Wiese. 11 records from Benthic fauna in the Pechora Sea (EurOBIS). 127 records from AKG-Gelände (Bensheim). 212 records from Gelände des IVL (Zeckern). 198 records from Innenstadt Göttingen - Natur Zuhause. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 198360 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 306369 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 248503 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 207 records from Cuxhavener Küstenheiden. 287806 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 122 records from Seewasen. 49406 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 88 records from Schussenaue bei Berg. 5 records from Schulgelände Lise Meitner Realschule (Paderborn). 44 records from Rur. 10 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 171 records from Landschaftspflegehof (Berlin). 17 records from Waldwiese. 612 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 86 records from Lebensraum Stadt und Park. 15 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 84 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 3 records from Carabidae of the Carpathians. 1619 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 37 records from Benthos counted on dredged samples during Valdivia cruise VA44. 2 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 119 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Black Poplar survey. 3496 records from Bioimages. 2 records from Nivå Bay species list, Zealand, Denmark. 213 records from Korean Peninsula Flora. 8 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 3 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 29090 records from Harvard University Herbaria. 9139 records from Árboles y Arbustos Nativos para la Restauración Ecológica y Reforestación de México (IE-DF,UNAM). 35 records from Deutsche Schule Budapest. 47996 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 22 records from Geführte Wanderung im Eselsbachtal. 139 records from The Distribution Atlas of Butterflies in Poland. 2 records from Wasserbachsee. 50 records from Unterbrucker Weiher. 131 records from Altenburg bei Bamberg. 765 records from crsn_data. 31 records from NABUGEO1. 12 records from Angelberger Forst - Klassen 3 a und 3 b. 150 records from Pottundkopp. 32 records from Wir erkunden die Hofau, Klasse 5c. 79339 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 164135 records from The Flora of County Wexford. 56476 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 227822 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 2 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 140 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 6 records from Invertebrate Zoology Division, Yale Peabody Museum. 46231 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 40414 records from University of Alberta Vascular Plant Herbarium (ALTA). 21 records from Förderzentrum Schmölln. 35 records from Kabelskebach (Kabelsketal, Saalkreis). 42806 records from The census of national forest of Benin .. 24 records from Nationalpark Harz Schul-AG Braunlage. 66 records from Die Teiche im Britzer Garten. 159 records from Kohlstattbrunnental. 4511 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 3 records from Lichen herbarium, UiB. 46 records from Wulfsmuehle/Pinnau. 2045 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 36 records from Icota - Pelagant. 7457 records from Andes to Amazon Biodiversity Program. 166448 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 201 records from renaturierter Main (Kemmern bei Bamberg). 14706 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 33 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12428 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 61 records from Wiese und Weide am Waldrand von Gusterath. 277 records from Gurgltal (Tarrenz). 175598 records from Vascular Plant Herbarium, Trondheim (TRH). 13 records from (Table 13) Benthic foraminifera in early-mid Miocene sediments of DSDP Hole 90-592. 23 records from Borkhart. 94 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 24 records from Naturpark Kottenforst-Ville 19.6.09. 24 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 14 records from (Table 18) Ranges of benthic foraminifers through the Neogene in DSDP Hole 23-219. 2262 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 89725 records from Allan Herbarium (CHR). 55 records from Rund um das LUGY. 3 records from Tümpel Schulbiologiezentrum. 10864 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 30 records from Hüttenseepark (Meißendorf). 60 records from Hintere Halde. 140 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 7815 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 19778 records from Colección del Herbario PSO de la Universidad de Nariño. 8 records from Warnowufer Groß Klein. 52 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 117-728A. 50 records from Steinbruch Pluwig. 7 records from Lichen Collection - University of Washington Herbarium (WTU). 132 records from European Molecular Biology Laboratory Australian Mirror. 386786 records from Meadow and Pasture Inventory (SJV). 218 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 746 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 45442 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 114 records from Am Moosangerweg. 1 records from KUBI Invertebrate Zoology Collection. 2146 records from Herbario de la Universidad de Sevilla, SEV. 16868 records from Kochi Prefectural Makino Botanical Garden. 4 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 545 records from OUPR - Herbário "Professor José Badini". 532 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 147 records from Merseyside BioBank - Merseyside BioBank NBN Frequently Updated Taxa. 28 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 118 records from Klasse 3a. 212 records from INERA-Luki reservation herbarium (CABIN project). 26658 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 8933 records from Green Plant Herbarium (TRT). 8 records from Schulteich Heinrich-Mann-Schule. 3 records from Privatteich(St.Leon). 2724 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 20 records from Neptune Deep-Sea Microfossil Occurrence Database. 21 records from Unser Schulhof. 52 records from CUMV Amphibian Collection (Arctos). 62973 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 4 records from Observaciones de Especies Silvestres (by Charif Tala). 9362 records from BioGIS - Vascular plants - SPNI. 887 records from JOIw - Xiloteca Joinvillea. 1 records from Haslauer Moor. 18245 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 27 records from (Table 17) Ranges of benthic foraminifers through the late Neogene in ODP Hole 115-713A. 82 records from Naturschutzgebiet Lochbusch-Königswiesen. 22 records from Liether Park (LMS), 6b. 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 317 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 23 records from MAL. 299 records from Macroinvertebrate abundance in river biotopes across England and Wales. 61 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 14 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 8 records from Schutzgebiet Ochtersum. 12 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 101 records from Frauenholz (Holzmaden). 132 records from Werremündung im Schwarzatal. 62 records from VFD-RP, Taunus: Bergweide Dehe. 1 records from Collection Crustacea NHCY. 3229 records from Florística de áreas protegidas en el estado de Durango. 102 records from Urwald 1 (Bad Waldsee). 12004 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 2511 records from Nature Locator - PlantTracker data from 2012 onwards. 1674 records from Aggregate Industries - Grassland and Heathland Survey at Bardon Hill 2008/9. 187 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 17 records from Naturerfahrung. 782 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 19 records from Levantamento de Herbáceas da RDS Uatumã. 97 records from Artenvielfalt im Beckerbruch (Dessau). 28 records from Liether Park (LMS), 6g. 75 records from Muehlenbach bei Friesheim. 356 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1914 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 7 records from CUMV Fish Collection (Arctos). 20 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 1714 records from Las especies endémicas de plantas en el estado de Jalisco, su distribución y conservación. 3 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 51 records from Streuobstwiese Kattenhund (Schleswig). 16441 records from SPF - Herbário da Universidade de São Paulo. 49 records from Schrebergarten Düsseldorf Oberkassel. 103406 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 37 records from Schulumgebung Grüterschule, Rheine. 3 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 6 records from Invertebrate Paleontology Division, Yale Peabody Museum. 2 records from Spechtwald. 1 records from Karpfenteich, Klasse 6d. 491 records from LBV 100 - Artenvielfalt am Rothsee. 4 records from UAM Invertebrate Collection (Arctos). 9 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 863 records from Red list project inventory, vascular plants. 13 records from Benthic foraminifera abundance of Hole 84-567A. 41 records from Hertfordshire Biological Records Centre - HBRC Wildlife Site Surveys, Hertfordshire. 28 records from inta-herbario-bab. 1609 records from CESJ - Herbário Leopoldo Krieger. 196 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 45 records from Isartal Dingolfing. 29 records from Wiesen am Treffpunkt Freizeit. 10492 records from Formación del banco de datos del herbario (UCAM). 255 records from Artròpodes d'Andorra. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 135 records from Bernhardsthal. 858 records from BioBlitz Barcelona 2010-14. 132 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 9 records from Spandau HBO. 3948 records from tan-database. 68 records from Teich im Wald zwischen Böblingen und Schönaich. 4 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 91147 records from Tiroler Landesmuseum Ferdinandeum. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 5 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 140 records from Artenvielfalt Kreis Gießen. 5 records from (Table 1) Absolute abundances of benthic foraminifera in ODP Site 120-747. 306 records from Gemeindegebiet Weikendorf (Marchfeld). 2 records from Bryophyte Collection - University of Washington Herbarium (WTU). 7 records from Herbarium specimens of Limoges university (LIMO). 14359 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1041 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 86609 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 67 records from Schulgelände des Schulzentrums am Himmelsbarg. 1 records from KNWR Entomology Collection. 348 records from Colección de referencia del Herbario CUVC de la Universidad del Valle. 113 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 1565611 records from SA Flora (BDBSA). 3629 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 960 records from Freshwater plants of Cameroon. 8 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 81 records from Schieferbrüche. 1098 records from Pinos del Noreste de México (UANL). 2 records from Familientag am Schorberg. 223 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Plantas vasculares. 42 records from (Appendix C) Distribution of benthic foraminifera in surface sediments from the Chatham Rise. 53 records from Gymnicher Mühle. 1453 records from HVAT - Herbário do Vale do Taquari. 35 records from MVZ Herp Collection (Arctos). 113 records from Botanical Museum, Copenhagen, the Phycology Herbarium. 120 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 68264 records from Herbario Amazónico Colombiano. 1096 records from SWECO. 4153 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 14 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 29 records from Königsdorfer Wald. 93 records from Steinbruch Haas Stuttgart-Münster. 29 records from Varnhalt. 63 records from Rund ums Cani. 108 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 90 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 25 records from UAM Earth Sciences Collection (Arctos). 34 records from Lech 2001. 16 records from Mittelstreifen. 14 records from Steinbachtal (Würzburg). 522780 records from Lund Botanical Museum (LD). 95 records from Döchtbühlwald (Bad Waldsee). 228 records from Estudio sistemático y ecológico del género Tigridia (Iridaceae). 170 records from EEIKO Base de datos sobre plantas invasoras. 2245 records from HEPH - Herbário Ezechias Paulo Heringer. 38 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 174 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 17 records from Artenvielfalt im Umfeld der Burgwegschule. 21429 records from Botanical Society of the British Isles - SNH Site Condition Monitoring - Vascular plants (2000-2006). 3195 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 6428 records from Nijmegen Natural History Museum (NL) - Herbarium. 3178 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 477 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 29 records from Colección del Herbario del Jardín Botánico de la Universidad Nacional de Colombia Sede Caribe. 393 records from Herbario Virtual Bosques Secos de Colombia - Sección Herbario Universidad de Córdoba (HUC). 98 records from Brock University Herbarium (BU). 64 records from Landschaftsschutzgebiet Buchhorst 3. 6 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 1 records from BIRDRACE Guckers Offenbach. 80 records from NSG Nollig. 5945 records from BioFresh Pond Data. 420316 records from Vascular Plant Herbarium, Oslo (O). 4 records from Foraminifera abundance of Hole 57-440B. 495 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 423 records from Sistemática del género Polianthes L (Agavaceae). 9 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 610 records from INRA-Versailles Arabidopsis natural variants. 56 records from Schulgarten Hans-Carossa-Oberschule. 20 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 149 records from Sonnentaugemeinschaft. 1550 records from Banco de Germoplasma del Jardín Botánico Atlántico. 41 records from Bolzplatz. 109 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 85 records from Exkursion Ebertsheimer/Grünstädter Berg. 169 records from Umgebung der Gesamtschule Hamburg-Winterhude. 30 records from Tab. 6: Relative Abundanz einzelner Arten der Endofauna. 15 records from Swiss Psyllid (Hemiptera) Collections - Basel. 58 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramos "Guantiva -La Rusia", Colombia. 38 records from Schulgelände SGD/Viersen. 38 records from Georgs-Padd (Wangerooge). 211 records from Wilson Botanical Garden - Las Cruces Biological Station. 4 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 161715 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 48 records from GymnQuerfurt. 22697 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 1968 records from Inventario Español de Especies Terrestres (MAGRAMA). 3551 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 20 records from Mühlenbach bei Buxtehude. 998 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 37931 records from Jardín Botánico de Córdoba: Herbarium COA. 622 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Himalayan Balsam Survey. 23 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 364 records from published_chenopodium_vulvaria_observations. 1023 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 9013 records from MfN - Fossil plants (Cenophytic). 5499 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from Coastal and marine species. 139 records from FFH-Gebiet "Calwer Heckengäu". 11 records from Höhle am Neuweg / Sächsische Schweiz. 37 records from Reifrocknarzissenwiese Löcknitz. 23 records from Streuobstwiese RSG (Cham). 305 records from Unna-Mühlhausen, Wiesen. 10588 records from SPSF - Herbário Dom Bento José Pickel. 2 records from Lerchenauer Baggersee (München). 1422 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 2207 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 298 records from KNWR Herbarium Collection. 1015 records from Caracterización vegetal y rasgos funcionales de plantas colectadas en un gradiente altitudinal de bosque altoandino a páramo en el Santuario de Fauna y Flora Iguaque. 53713 records from Colorado State University Herbarium. 5156 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 1315 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 7843 records from Louisiana State University Herbarium - Vascular Plants. 4712 records from HAMAB - Herbário Amapaense. 86 records from Waldstück Bremerhagen LK Bio Kl. 12. 45 records from Landschaftsschutzgebiet Buchhorst 4. 1 records from BIRDRACE Die Schwenker-Birder. 1 records from Kleinod unter Hochspannung. 50 records from Scottish Natural Heritage - Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 83 records from Trockenhang Greinhartsberg Edelfingen. 200 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 14 records from AKG-Bensheim. 158 records from Lebensraum Gesamtschule (Langerwehe). 83 records from "Tre Pini" (Montebelluna, Italien). 61 records from Wismar Bucht coast-watching. 3255 records from NHT_flora. 789 records from Herbier_CNSF. 642 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Countryside Council for Wales - Bullhead Survey Data in Wales. 6761 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 5 records from UCM Amphibian and Reptile Collection (Arctos). 3 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 150 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 16 records from Coleoptera of Biebrza National Park. 105432 records from Instituto de Ciencias Naturales. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 51332 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1410 records from MfN - Fossil plants (Mesophytic). 147 records from Schule Sulzbach (Oberegg). 169 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 2408 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 3184 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 467 records from Monitoring data from the federal state Saxony (Germany). 4 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE218. 131 records from Lindau im Bodensee. 64149 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 3098 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 22761 records from Paleobiology Database. 4 records from Real Jardin Botanico, Madrid: MA-Lichen. 1 records from Benthic foraminifera abundance of Hole 34-320. 10 records from Foraminifera abundance of Hole 59-448. 16 records from Biological Records Centre - Derek Lott Coleoptera Dataset. 1 records from Die Milbenfauna der Nordseeinsel Wangerooge. 50275 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 215 records from Weinberg Reichersdorf. 2 records from Wie viel Natur gibt es im Park?. 325 records from Neckartalsüdhang (Horb). 65 records from Fuchsloch (Mohlsdorf/Ostthüringen). 175 records from Entomological collections, UiB. 4 records from Collection Crustacea - ZMB. 166448 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 749 records from Inventaire National du Patrimoine Naturel : CBN Alpin de Gap. 47996 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 420 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 2781 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 2864 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 38 records from "Schlechteberg" Ebersbach/Sa.. 58 records from Schulgarten mit Klasse 8a (Essen). 38 records from Ludwigshofen. 45 records from Ober-Olmer Wald. 725 records from Naturhistorisches Museum Mainz, Botanical Collection. 140 records from Stausee (Oberdigisheim/Meßstetten). 261 records from Herbier Boreal Confluence (BOUM). 40041 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 3137 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 47 records from Schulwald Grundschule Brügge. 38 records from Aktion der Klasse H2 in Simmelsberg. 23 records from NCOS1959_Crustacea (OBIS China). 1831 records from Threatened Species programme. 1118 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 319 records from An updated checklist of aquatic plants of Myanmar and Thailand. 304 records from Walldorf-Wiesloch: "Natur über den Gleisen". 39914 records from Cartographie des Leguminosae (Fabaceae) en France. 13 records from Meiobenthos of target sites of Crimea in 2009/2010. 287 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 4475 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 24 records from (Table 3) Benthic foraminifera in early-middle Miocene sediments of DSDP Site 89-586. 425 records from Erlengraben/Lipp-Tal (Östringen). 7 records from Coleoptera of Kozienice Forest. 4893 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 1 records from Naturalis National Natural History Museum (NL) – Coelenterata. 122980 records from BioGIS - Vascular plants - A. Danin's grid database. 33 records from Likona Invertebrates. 18 records from Liether Park (LMS), 5a. 35 records from Seeufer ehem. BUGA-Gelände. 1136 records from API_CRSN_Data. 1 records from Museum Victoria provider for OZCAM. 129 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 41 records from Wiesen in der Grünen Mitte. 21 records from (Table 14) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-592. 3165 records from Inventario florístico de la Sierra de Huautla, Morelos. 20 records from Fungi (S). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 2 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 146 records from Gieselbachtal Fulda-Harmerz. 120 records from Baggerseen bei Krauchenwies. 1387 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 433 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 10 records from Fluss - Vielfalt. 94 records from 4. GEO-Tag in Eberbach. 17 records from Nottinghamshire Biological and Geological Records Centre - UK abstract from Nottingham City Museums & Galleries (NCMG) Insect Collection Baseline database. 66 records from Tartu University, palaeontology collections. 14666 records from New Zealand Biodiversity Recording Network. 4 records from Bumblebees, cuckoobees and butterflies in southern Poland. 29 records from Feriendorf Ober-Seemen. 81 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 82 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 16 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 1 records from Tauchaktion. 3 records from Plan de vertebrados de la Patagonia. 29 records from Waldsee. 112 records from Hochschulgelände (Bremen). 61 records from Hochschule Zittau/Görlitz. 34 records from Überschwemmungsgebiet der Wied. 8921 records from HUFU - Herbarium Uberlandense. 58 records from Dorfrand Mauderode. 1336 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 157 records from Pflanzen und Tiere im Burgwald. 87 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 8211 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 7540 records from Botany registration database by Danish botanists. 43382 records from University of Ghana - Ghana Herbarium. 25 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 1 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 3303 records from Vascular Herbarium, NMBU. 7 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 37943 records from MBML-Herbario - Herbário Mello Leitão. 29330 records from Colección Herbario Federico Medem Bogotá - FMB. 5 records from Aktion des Romain-Rolland-Gymnasiums. 8 records from Auenwiesen und Trockenrasen. 3 records from Schulbiotop und Brigach (Villingen). 4062 records from Ireland's BioBlitz 2012. 1480549 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 23 records from Ackerrain Plönhagen. 143 records from Faberpark (Nürnberg/Stein). 1 records from Queen Victoria Museum Art Gallery provider for OZCAM. 35 records from FFH-Gebiet Klosterwasser/Burkau. 378 records from Inventaire National du Patrimoine Naturel : CBN Brest. 51 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 1023 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 930 records from Botanic Garden of the Finnish Museum of Natural History. 65 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 28 records from 8c. 32 records from Sternwiese Mülheim-Broich. 250 records from IBF Monitoring of Fungi. 11 records from Waldstück am Schullandheim Bad Bederkesa. 1025 records from tef-database. 10 records from (Table 7) Relative abundance of benthic foraminifera in ODP Site 112-683. 194 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 1589 records from Nijmegen Natural History Museum (NL) – Herbarium. 118 records from VFD-H: Rheingau: Pferdeweide Loock. 3 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B. 25 records from Sandgrube Zaisertshofen. 49 records from Illinois Natural History Survey Insect Collection. 2453 records from The Fungal Collection at the Botanische Staatssammlung München. 10284 records from MBM - Herbário do Museu Botânico Municipal. 1336 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 27 records from Benthic foraminifera abundance of Hole 84-569, Part 1. 243 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 1629571 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 28 records from Nationalpark Harz Juniorranger. 103 records from Scottish Environment Protection Agency - Scottish river macro-invertebrate records from 2007 collected by SEPA. 1 records from Regenwasserabfangbecken Erlenbach. 1178 records from EDIT - ATBI in Gemer area (Slovakia). 4660 records from National Museum of Natural Science. 10939 records from Dataset of Phenology of flora of mediterranean high-mountains meadows (Sierra Nevada). 139 records from FNL e.V.. 18 records from Liether Park 2 (LMS), Klasse 6c. 605417 records from New Zealand National Vegetation Survey Databank. 4 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 6083 records from University of Lethbridge Herbarium (LEA). 65 records from Naturgrundstück (Eutin). 1 records from Bach. 62 records from Haarbach Höfe. 3 records from "Am Riedert" im Westerzgebirge. 2378 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 1 records from LUNG-Naturwiese. 6415 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 2 records from Sistematización de la Colección Paleontológica de la Facultad de Ingeniería, UNAM. 68 records from Artenvielfalt auf den Elbwiesen (Dessau). 112 records from Schussenaue (Weingarten). 370839 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 44383 records from IAC - Herbário do Instituto Agronômico de Campinas. 8 records from MfN - Fossil invertebrates IIb. 881 records from Vascular Plants Collection of National Museum of Nature and Science. 1559 records from Florística de la reserva de la biósfera de Mapimí. 8 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 10710 records from EAC - Herbário Prisco Bezerra. 99 records from Außengelände KITA "Mäuseburg" Waldkirchen. 4268 records from Flora Novo Galiciana-Gramineae. 345370 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 27 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2469 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 2875 records from Geneva Herbarium – Burnat Herbarium (G-BU). 69 records from Wirbach. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE275. 138208 records from Vascular Plant Collection. 64 records from Überall ist Wunderland. 2612 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 1199 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1050 records from Plantas Acuáticas de la Orinoquía Colombiana. 8770 records from Harriet Irving Botanical Gardens (HIBG). 149793 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 67 records from VFD-RP: Taunus: Ponykoppel Thurner. 186 records from Schlichemquelle (Tieringen/Meßstetten). 6855 records from UESC - Herbário Universidade Estadual de Santa Cruz. 23 records from Örtzemündung (Stedden). 55 records from Niveles y patrones de variación genética del género Abies en México. 1003 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 97 records from Entdeckertour am Muldestausee. 33030 records from FURB - Herbário Dr. Roberto Miguel Klein. 253539 records from National Forest Inventory (SLU). 2 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 7 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 86266 records from The AAU Herbarium Database. 19 records from IndOBIS, Indian Ocean Node of OBIS. 34806 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 2793 records from HDJF - Herbário Dendrológico Jeanine Felfili. 1 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 18 records from (Table 6) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-590B. 536 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 32545 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 84 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 57 records from Wedeler Au. 253 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 36 records from Schulhof Liebfrauenschule Oldenburg. 50 records from Hoher Stein Kallenhardt. 133 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 254 records from Australian Antarctic Division Herbarium. 62 records from Natur aus zweiter Hand am Muldestausee. 61 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 140 records from Mißmahlsche Anlage. 136 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 2877 records from HTSA - Herbário do Trópico Semiárido. 16 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 32 records from New records for Albania based on taxa from the Prespa National Park. 1156 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 353 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 5183416 records from Artdata. 1 records from BIRDRACE Unterste Niederrhein-Rennvögel. 3411 records from Herbier de Wallis et Futuna. 4431 records from WII Herbarium Dataset. 91 records from Naturhausgarten. 4325 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 16 records from Schulgelände (Wetter). 110 records from Naturschutzgebiet Bausenberg (Niederzissen). 1102 records from Plantas laguna El Tinije. 2 records from HUEG - Herbário da Universidade Estadual de Goiás. 69 records from Dreilinden Gymnasium-Schulgelände. 1 records from Heckenstreifen am Zehntbergweg. 142953 records from CONN. 8 records from Willersalpe. 29 records from Park Schönfeld (Kassel). 1 records from Die Bachspezies 2008/2009. 16 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE241. 1692 records from Census of plant species in Monts-Kouffè regions, center Benin. 2 records from Tiere im Teichgebiet. 1257 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 35 records from Wasserwerkspark (Chemnitz). 6 records from Kaisertal. 39 records from Wälder im Hainbachtal. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 3 records from Fungi Collection. 1298 records from Estonian University of Life Sciences. 19846101 records from INPN - Données flore des CBN agrégées par la FCBN. 39 records from invertebratezoology. 131 records from Renaturierung Werse (Innenbereich Beckum). 1 records from Schulgarten Waldorfschule Hassfurt. 283 records from Naturschutzstation Schmidsfelden. 548228 records from Nationaal Herbarium Nederland. 96 records from TRTE Herbarium (TRTE). 9 records from Occurrences des observations de la campagne Suivi Aérien de la Mégafaune Marine en France métropolitaine (SAMM1 - Hiver 2011/2012). 99 records from Schulgarten Huttenheim (Philippsburg/Baden). 50520 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1369 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1 records from Streuobstwiese Alt Necheln. 623 records from Herbier de Strasbourg. 153 records from Eschlberg Thalhausen. 337 records from Herbarium Specimens of Bonin and Ryukyu Islands. 25137 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 46 records from Rare vascular plant species in North-West of Kostroma region, Russia. 8005 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from Christopher Walker collection of Glomeromycotan fungi. 25 records from Hainbachtal bei Oelsnitz / V.. 531 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 48 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 1320 records from Herbier National de Mauritanie (HNM). 106 records from vegoek. 22 records from Mittelriede Höhe Gliesmarode-Braunschweig. 1 records from Wattuntersuchung (Cuxhaven). 209 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 273 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 104 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 63 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 103 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 2 records from uno city. 564 records from Central Scotland Forest Trust - Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 691 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7423 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 264 records from Dornwanger Moos. 34754 records from Herbario del CIBNOR. 4 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 102917 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 251 records from Powys Flora Conservation - Welsh Orchid Survey 2009. 7 records from Ohemoor (Hamburg/Norderstedt). 36 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 99407 records from Plants of Papua New Guinea. 18 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 48 records from Sandhofen. 10042 records from Census of the flora of Benin. 203 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 650 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 1 records from Birdrace_Schräge_Vögel-Herford. 45 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 2088 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 12 records from Klosterwald Itzehoe. 8639 records from Herbarium of the Université Libre de Bruxelles. 21058 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 910 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 4882 records from Universidad Autónoma de Madrid, Biología, Acalypha. 287 records from Tag der Artenvielfalt im Taubental. 22330 records from IICT Herbário LISC. 30 records from Naturpark Kottenforst-Ville 15.6.09. 786 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 1 records from KTU Pteridophyta. 88 records from Tallinn Botanic Garden. 12 records from Alter Nördlicher Friedhof (München). 11 records from Waldgebiet Todtnau- Sonnhalde. 101 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 934 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Japanese Knotweed Survey. 1 records from Microbial Culture Collection, National Institute for Environmental Studies. 170 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 35 records from Lebensraum Walram. 15995 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 168 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Acahuales. 38 records from AIMS - Bioresources Library (OBIS Australia). 142 records from Kiesbagger (Mittelhausen). 60 records from Benthic foraminifera abundance of Hole 84-568, Part 2. 254 records from Freiburger Netzwerk Artenvielfalt. 343 records from Investigaciones sobre recursos no maderables de México: biología evolutiva y conservación de plantas del género Chamaedorea. 64 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 18140 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 384 records from Posidonia Oceanica Survey 2005 (EurOBIS). 10616 records from Fieldjournal.org observation database. 13 records from (Table 19) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-593. 17430 records from ICN - Herbário do Instituto de Ciências Naturais. 4 records from Regenwasserabfangbecken. 239 records from Insekten Sachsen. 1719 records from Inventario florístico de la Sierra de San Carlos, Tamps. 439 records from Continuous Plankton Recorder database. 15 records from Artenvielfalt der Nordsee - Sylt. 229018 records from Wetland Inventory (NV). 27 records from Artenvielfalt in der Kinderakademie im RFZ. 5805 records from MAR - Herbário do Maranhão. 1 records from Carpatica Operation. 4794 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 1 records from Der Kreuzenzian und sein Bläuling. 444 records from Naturschutzgebiet Bausenberg. 54 records from Biotop Binsenwiesen (Wehrheim/Taunus). 3 records from Benthic foraminifera abundance of Hole 84-567. 87438 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 3 records from Kurler Busch (Scharnhorst). 529 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 226 records from Schwanheimer Wald. 53 records from VFD-H: MIttelgebirgsweide. 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 3 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Diptera Records up to Dec 2011. 1356 records from Anymals+plants - Citizen Science Data. 61 records from Alien Species in Poland - Plants. 465 records from Freiburger GEO-Tag der Artenvielfalt. 208 records from Herbarium of Lars Levi Laestadius. 71 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 376 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 6190 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 128631 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 424 records from Herbier L. Mulon (BOUM). 12 records from MICROBIS database. 75 records from Leben im Finkensteiner Moor. 282 records from GEO Biodiversity Day. 9 records from Lichen Herbarium Berlin. 90 records from Naturnahes Tal in Siena. 1169 records from Southern Cape herbarium. 2072 records from HUCS - Herbário da Universidade de Caxias do Sul. 51 records from Balkon (Norderstedt). 52 records from Rund ums Schulgelände. 3 records from Benthic macrofauna abundance of subcores of sediment core 13200-045. 414925 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 7 records from Distribution of benthic foraminifera of sediment core PS1388-3. 58 records from LISU Herbario Angola. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 30 records from Fledermaus. 9 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 1041 records from Botanical Research Intitute of Texas. 24897 records from Herbarium Berolinense. 220 records from Artenfülle um das Schalkenmehrener Maar. 35 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 45 records from Mauernacker (Wettsaasen). 25 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 262 records from IBF Monitoring of Plant Galls. 28 records from Schriesheimer Steinbruch. 5 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part I. 11 records from BIOLOGICAL SCIENCES DATA. 42 records from Kindervilla Außengelände. 180797 records from National vegetation diversity inventory and mapping plan. 167 records from Naturpark Sternberger Seenland. 28195 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 23 records from Artenvielfalt auf Zollverein. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2 records from Collection Tunicata SMF. 2 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 32 records from Aktion Wiese und Wegrain Gitzenheide. 163 records from katzenbuckel. 49 records from Schulhof Goethe-Gymnasium (Emmendingen). 117 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 4801 records from HUTO - Herbário da Universidade de Tocantins. 1 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 1 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 4376 records from Colección Herbario Universidad Católica de Oriente. 34 records from Tag der Artenvielfalt BUND Kaiserslautern. 16 records from Collection Aves (bird skeletons) SMF. 127 records from Expedition "Schulgelände". 1014 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás, Tamaulipas. 206 records from schulgarten. 5701 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 46 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 11 records from Feuchtwiese Grüne Mitte, Klasse 5a. 2392 records from Estudio monográfico de la familia Rhamnaceae en México. 461 records from Gemeinde Sursee. 139 records from Quarrendorfer Landschaftsschutzgebiet. 3 records from EcoRecord - Bird records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2721 records from PACA-AGP - Herbarium Anchieta. 3 records from Streuobstwiese. 26 records from Naturpark Kottenforst-Ville 16.6.09. 78 records from Gelände des Schulzentrums am Himmelsbarg. 19 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 6491 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 119733 records from Field Museum of Natural History (Botany) Seed Plant Collection. 121 records from Biosphäre Bliesgau. 8 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 87 records from Himmelmoor. 59 records from Industriebrache (Kempen). 96 records from Artenvielfalt am "Grünen Band" bei Coburg: 20 Jahre Wiedervereinigung. 35042 records from Instituto de ciencias naturales. 4612 records from SysTax - Herbaria. 9 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 7 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 2460 records from VIC - Herbário da Universidade Federal de Viçosa. 4 records from Wanninchen. 7 records from MarBEF Publication Series data (EurOBIS). 4437590 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 31 records from Langes Tannen in Uetersen. 540958 records from Aarhus University Palm Transect Database. 430 records from Phanérogames recensés aux Monts Nimba. 1914 records from SJRP - Herbário de São José do Rio Preto. 3 records from Occurence of foraminifera and other microfossils in sediment core CRP-2/2A (Table 1). 19119 records from H.A. Stephens Herbarium. 1 records from Foraminifera abundance of Hole 59-451. 200 records from MEXU/Pinaceae. 32 records from Flora und Fauna am Mittelrheintal. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 126 records from Lustbach-Umland. 81 records from VFD-H: Heidenrod: Weide am Ortsrand. 750 records from Inventaire National du Patrimoine Naturel : CBN Méditerranéen de Porquerolles. 485 records from Schlern - (Bozen). 49 records from Unser Schulgelände. 695 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 87 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2079 records from Flora vascular acuática de la cuenca del Río Tamesí. 138 records from Kiesgruben Wemb. 172 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 8 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 80 records from Pfingstexkursion Alter Bessin. 486 records from Galapagos grasses and sedges. 16298 records from Polish gene bank – passport data of plants accessions which are important in human life. 489265 records from Consortium of California Herbaria. 382 records from Lustadter Wald .. 1208 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 20 records from Schulaktion des Dienzenhofer-Gymnasiums. 323 records from Levantamento do estrato arbustivo da vegetação de campina do RDS Uatumã. 186 records from Deponie Klausdorf. 49 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 2664 records from All observations extracted from the Flora of Northumberland and Durham 1831. 51 records from Crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 20 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 27 records from (Table 15) Ranges of benthic foraminifers through the early-middle Miocene in ODP Hole 115-709A. 37 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 72 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 427 records from GEO-Hauptveranstaltung in "Wildtierland". 150 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 57 records from Schulgelände Städtisches Gymnasium. 3 records from Stadtrandlandschaft Apolda-Nord. 63 records from "Ahrschleife bei Altenahr". 3956 records from Rye, Barley, Oats Genetic Resources. N.I.Vavilov Research Institute of Plant Industry, St. Petersburg. 16 records from Liether Park (LMS), 6c. 9428 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 87 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 3049 records from Composición florística del Parque Nacional Huatulco. 3531 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 10949 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 3502 records from UFG - Herbário da Universidade Federal de Goiás. 76 records from Streuobstwiese Stedar 2009. 86 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 65 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 80 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 11 records from Exkursion in der Ehrbachklamm/ an den Erbach. 831 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 5676 records from PlutoF platform observations. 2031789 records from Missouri Botanical Garden. 6 records from Collection Pisces SMF. 138 records from Wald und Wiese am Buchwald. 15 records from Südpark (Bochum-Wattenscheid). 38 records from "Schwarzes Teich" (Waldpark Radebeul). 240 records from NSG Karwendel. 768215 records from Norwegian Species Observation Service. 96710 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 8 records from MEXU/Colección Histórica. 194 records from Streuobstwiese Kugelberg (Ulm). 142 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 176342 records from Atlas des plantes vasculaires de Lorraine. 364 records from Naturschutzgebiet Lüneburger Heide. 43 records from Amtsrain Apolda-Zottelstedt. 1 records from Wälder und Seen rund um den Mühlenberg. 339871 records from Donnees ONF Faune-Flore-Fonge. 9 records from Kleinstbiotop mit Schulteich/Weißwasser. 1 records from Chenopodium vulvaria. 74 records from Schulwald Marksuhl. 105 records from "Schwarzwassertal" bei Pobershau. 73 records from Kloster Eberbach. 6 records from GEO-Hauptveranstaltung Bodden (Vilm). 71 records from Tornoer Teich. 448447 records from naturgucker. 2829 records from Specimen Database of Colorado Vascular Plants. 50 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 32400 records from ASE - Herbário da Universidade Federal de Sergipe. 1 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 2144 records from CVRD - Herbário da Reserva Natural Vale. 305 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 13783 records from Irish Crop Wild Relative Database. 13916 records from West-, Central- and East African Plants Databases. 147 records from Heinersdorfer Sumpfwiese. 840 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 1752 records from Estonian Museum of Natural History. 10583 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 35 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 202 records from AIS Wildtype Populations of Arabidopsis. 4904 records from Michigan State University Herbarium Vascular Plants. 360015 records from Species data extracted from the National Vegetation Database. 186 records from Küstenschutzwald. 19 records from Uferzone Wipper (Biesenrode). 88 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 95292 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 35381 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 4642 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 93 records from Prophetensee Quickborn. 630 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 25 records from Foraminifera abundance of Hole 55-433A. 58 records from USGS NRP - Submerged Aquatic Plants - 1966-2009. 161 records from Bioblitz 2013 Copenhagen Denmark. 34 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 326 records from Sudeniederung (Amt Neuhaus). 5 records from Queensland Museum provider for OZCAM. 545920 records from Australian National Herbarium (CANB). 424 records from BUND - Dassower See (Lübeck/Dassow). 2 records from Upper Silesian Museum, Bird Observations. 198 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 4473 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 14813 records from CPAP - Herbário CPAP. 35 records from Saproxylic Beetles of Ireland. 723 records from Continuous Plankton Recorder Dataset (SAHFOS). 25 records from BB-Biodiversität a. 7 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 170051 records from The System-wide Information Network for Genetic Resources (SINGER). 72580 records from Scottish Natural Heritage - Standing Waters Database. 118 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 4 records from Naturschutzgebiet Ahrschleife (Altenahr). 35 records from Lebensraum Dorf. 4 records from Vigna pandeyana (Fabaceae), a new species from northern Western Ghats, India. 7 records from Weddell Sea macrozoobenthos EASIZ I. 896 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 87425 records from EURISCO, The European Genetic Resources Search Catalogue. 17718 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 2 records from Foraminifera abundance of Hole 48-403. 81465 records from SINGER Coordinator. 41445 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 15 records from Kaltenkirchen Brache. 85 records from Binsenwiesen im Bizzenbachtal. 72 records from Botanischer Garten (Saarbrücken). 30 records from Töpinger Mischwald. 558617 records from Biological and palaeontological collection and observation data MNHNL. 76713 records from Herbarium of Taiwan Forestry Research Institute. 4979 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 13444 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 606930 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 3 records from Benthic macrofauna abundance and biomass in surface sediment during cruise CD86. 91207 records from Herbier de la Guyane. 41 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 1 records from NX - Herbário Nova Xavantina. 4 records from Flora und Fauna am Mühlberg. 71 records from Artenvielfalt des "Grünen Klassenzimmers". 586 records from MfN - Fossil plants (Paleophytic). 1749 records from EPA'S EMAP Database. 48 records from Schulprojekt (Bremen). 33 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 2 records from Herbier Louis-Marie (QFA) - Collection de lichens. 95 records from Artenvielfalt und Kulturlandschaft. 26 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 28419 records from University of Vienna, Institute for Botany - Herbarium WU. 2152 records from EFC - Herbário Escola de Florestas Curitiba. 11718 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 618 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 2 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE255. 25 records from Phragma-Thermis/Thessaloniki. 1660 records from HPL - Herbário do Jardim Botânico Plantarum. 1 records from Wiese hinter der Schule (Darmstadt). 98 records from Owere Fiddel. 275 records from Pilstingermoos. 22 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 57 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 126121 records from Tromsø Museum, Vascular plants. 231 records from Garten J. Scherrer (Lachen-Speyerdorf). 6954 records from Vascular plants collection of Hiratsuka City Museum. 2628 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 3 records from Grand Manan Basin Benthos (OBIS Canada). 168 records from Kremmer Luch. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 1149 records from Herbarium J Räsänen. 5241 records from Ecofact. 121792 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 4 records from Royal Horticultural Society - Records from the RHS insect reference collection. 13 records from Spielwiese. 4270 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 128 records from Stadt Königs Wusterhausen. 2122 records from Plant Systematics Laboratory, Ajou University, Korea. 67 records from Schulgelände Schule auf der Aue, Münster. 12 records from ELM paleontology. 74 records from Schulgarten Zinnowwald-Grundschule. 2777 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 167 records from Beweidungsprojekt an der Nesse. 1499 records from Pontaurus. 482337 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 3389 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 5 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 994 records from Herbarium of University of Białystok - Vascular Plants. 239 records from Wälder bei Nordkirchen. 1 records from "Schule am Inselsee" Güstrow. 96081 records from herbario. 7419 records from BioGIS - Vascular plants - Israeli Gene Bank. 5118 records from Caracterización del hábitat de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 83 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 9 records from Volkspark Prenzlauer Berg. 21 records from (Table 12) Ranges of benthic foraminifers through the Miocene in ODP Hole 115-707A. 48313 records from Biodiversitätsdatenbank des Landes Salzburg. 251 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 5182 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 766 records from Inventario nacional de especies vegetales y animales de uso artesanal. 5483 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 4605 records from Herbier Ecole de Faune. 744667 records from Flora Atlas N.T.. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 1170 records from NBI. 6 records from Kita-Wäldchen Fuchsturmweg Jena. 557 records from HBGSpermatophyta - Herbarium Hamburgense. 43 records from Insektenvielfalt Ahe/Weichelsee. 814 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 36 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 6 records from (Appendix Table 3) Distribution of live benthic foraminifera in surface sediments. 26 records from Tullie House Museum - Tullie House Museum Natural History Collections.. 5 records from SeamountsOnline (seamount biota) (CoML). 27942 records from Repatriación de datos del Herbario de Arizona (ARIZ). 9 records from (Table 4) Ranges of benthic foraminifers from the early Oligocene to the early Miocene in DSDP Hole 22-214. 15624 records from Brassicaceae of Canada. 36 records from Foraminifera abundance of Hole 57-438A. 17 records from Flora of Japan Specimen Database. 107 records from Artenvielfalt rund um die Dalbek-Schule. 102 records from EDIT - ATBI in Spreewald (Germany). 198 records from Diversidad y conservación del germoplasma de henequén Agave fourcroyedes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 38959 records from BioGIS - Vascular plants - A. Danin's point database. 20 records from Heilpflanzen im Hainbachtal. 100 records from Mangfalltal. 164133 records from The Flora of County Wexford. 152 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 212 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 131 records from Ökostation (Freiburg). 200536 records from iNaturalist research-grade observations. 23 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 3 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part I. 709 records from Flora acuática vascular del área focal Felipe Carrillo Puerto, Corredor Biológico Sian Ka'an-Calakmul, Quintana Roo, México. 1032 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 1 records from LBV-Kindergruppen Markt Tussenhausen. 7 records from TBW-Schafberg. 56848 records from inatura - Erlebnis Naturschau Dornbirn. 86 records from Klutensee. 79 records from Industriegebiet (Kempen). 16 records from Natural History Museum Rotterdam (NL) - Plantae collection. 13206 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 48 records from Wiesenbiotop am Wasserturm. 58 records from Naturschutzgebiet Kochertgraben. 83 records from VFD HH/SH "Pferdeweide Lemsahl". 12 records from (Table 16) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-710A. 247 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 72429 records from UB - Herbário da Universidade de Brasília. 60 records from NSG Forst Zinna-Jüterbog-Keilberg. 1 records from Gwaii Haanas Invertebrates (OBIS Canada). 28 records from Frau Voss. 1055479 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 16004 records from Species plots from the Norwegian Vegetation Mapping Programme. 5 records from Schulgarten der Hainbuchenschule (Hagenbach). 9 records from Bats of Poland. 347 records from Orchid Herbarium Collection. 10314 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 65 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 37 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 1 records from Im und um das Schulhaus. 189 records from Bannwald Burghauser Forst. 76 records from Steinbruch Kronungen. 1144 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 8272 records from Base de datos sobre la flora de Durango. 7122 records from MEXU/Asclepiadaceae. 148 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 32 records from Kochertgraben II. 166 records from Rohrmeistereiplateau und angrenzendes Gebiet. 31479 records from Flora of County Cavan. 5 records from Coleoptera of Swierklaniec Forest. 31 records from Urwald 3 (Bad Waldsee). 67 records from NCOS1959_Mollusca (OBIS China). 149 records from Berkel. 1 records from Field Museum of Natural History (Botany) Fungi Collection. 97 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 223100 records from Vascular Plants, Field notes, Trondheim (TRH). 7 records from Erhard Sopp. 13942 records from Bolus Herbarium. 43 records from Landschaftsschutzgebiet Schmutterwald. 969 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 2099 records from Herbario Museo de La Salle Bogotá (MLS). 4 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 64445 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 81 records from Sürther Aue. 23481 records from Swan Coastal Plain Survey. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 55 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 24 records from Erft in Selikum (Neuss). 220 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 46 records from Mauervegetation,Flechten und anderes. 57 records from Kaniswall/ Gosener Wiesen an der Spree. 242 records from Projekt Dellbrücker Heide. 78 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 8211 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 472237 records from NSW herbarium collection. 662 records from Marine Conservation Society - Seasearch Marine Surveys. 5439 records from University of California Museum of Paleontology. 13 records from Zoo Frankfurt. 13 records from Coleoptera of Tuchola Forest and Tuchola Forest National Park. 11 records from Lund Museum of Zoology (MZLU). 43620 records from UEC - Herbário da Universidade Estadual de Campinas. 35308 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1 records from Foraminifera abundance of Hole 39-357. 57 records from Ortelsbruch - Hangmoor bei Morbach. 28 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 5408 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 9365 records from Herbarium (Åbo Akademi), Centre for Biodiversity, University of Turku (TURA). 149 records from Wildkräuter. 324 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 91 records from Truppenübungsplatz Panzerkaserne Böblingen. 377657 records from IBF Monitoring of Vascular Plants. 2197 records from Dataflos. 27 records from Benthic foraminifera abundance of Hole 84-569. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 133 records from Tiergarten Straubing. 46814 records from E. C. Smith Herbarium (ACAD). 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 126 records from Umgebung der Grundschule Oderberg. 78 records from Feldweg Waldkirchen. 796 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 66 records from Siegen/ Gymnasium Am Löhrtor. 14 records from Hainbachtal in Oelsnitz/V.. 13 records from NPL collections. 855 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 24463 records from Natural History Museum, Vienna - Herbarium W. 20 records from Birkenpilz. 89859 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 2 records from Brenz (Heidenheim). 42 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 943 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 73 records from Biotop "Kohlbeke" (Berlin-Marzahn). 225 records from Ried und Sand - Artenvielfalt durch Beweidung. 9 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 6 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Invertebrate Observation Records other than Lepidoptera. Pre-2010 for Cumbria. 274 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 270 records from Wildes Bremer Leben im Park. 15 records from Database on Forest Disturbances in Europe. 24340 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 40921 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 34 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 64 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 51 records from Weidegut Rechab. 145524 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 21 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 54 records from Rund um die Sausenburg. 1 records from Parthenaue. 1002 records from National Biodiversity Data Bank. Observation records, 1900-2014. 129 records from Bodenseeufer Radolfzell. 32 records from Wiese und Bach beim Unterbecken (Markersbach). 732 records from Vertebrats d'Andorra. 47 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 1 records from Kohlbach (Sulzfeld). 60 records from Aktion - Friedensburg Oberschule. 63276 records from Canadian Museum of Nature Herbarium. 32480 records from Database of Native Plants in Taiwan. 5730 records from Herbarium Vonderau - FULD. 150 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 6657 records from Estudio taxonómico y base de datos del género Muhlenbergia de México. 15178 records from Ireland's BioBlitz. 21 records from Stadtbiotop Ulrichteich. 351 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 102 records from VSN-Wiese. 53539 records from PRECIS (KwaZulu-Natal Herbarium). 27 records from Flächennaturdenkmal Grubditz. 2 records from BIRDRACE Immerwiederhopf. 163 records from Wald am Schloss Wittgenstein Bad Laasphe. 11 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG95A. 52 records from Trockenrasen Franzigmark (Halle/Saale). 13045 records from Tullie House Museum - Tullie House Museum. Cumbria Wildlife Trust survey records from 1970 - 2007 of Cumbria Wildlife Sites. Various.. 34 records from Maschwiesen Laatzen. 365 records from 20 Jahre Naturschutzgebiet Dreienberg. 2403 records from CNMT - Herbário Centro Norte Mato Grossense. 1396 records from Diversidad florística y endemismo en la Reserva de la Biósfera El Cielo, Tamaulipas, México. 52 records from Rund um den Hainbergsee. 2 records from Trockenwiesen und angrenzender Waldrand im Hainbachtal. 185 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 65 records from Mainufer. 26 records from Stadtwald Heide. 3303 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 1023 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 452 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 166 records from Promberg1. 259557 records from Carnet en Ligne. 1 records from Biotop Alexander-von-Humboldt-Schule. 81 records from Wanderweg am Windebyer Noor (bei Eckernförde). 94 records from Halberg bei Neumorschen. 4 records from FCAB - Herbário Friburguense. 40 records from Roter Berg Werdau (Leubnitz). 165053 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 286939 records from Especímenes INBio. 53 records from Oschenberg, NO von Bayreuth-Laineck. 52 records from Birkenloh. 51 records from Gronau - auf der Suche nach dem Neunauge. 22 records from Unter hellen Zinnen und finsteren Grotten. 3 records from Benthic foraminiferal assemblages (living), surface data. 12 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 11044 records from EPA River Biologists data. 26942 records from MEXU/Colección de Plantas Acuáticas. 39578 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 35 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 483 records from Königstetten. 4406417 records from Observations du Conservatoire botanique national du Bassin parisien.. 57 records from Lichens of North-Eastern Poland. 19 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 2414 records from Census of plant species in Toffo forest reserve. 131 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 61 records from Raus in die Natur. 47 records from Biosphärenreservat Mittelelbe. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 77 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 44 records from Solanum_baretiae. 7221 records from Herbier du Bénin. 58403 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 197 records from Jardin botanique de Montréal (JBM). 212 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 67 records from Blumenrather Heide / Virneburg. 2 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 6458 records from Herbier CNRST/INERA. 4361 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 8 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688A. 28 records from Natural England - Species Surveillance Project - In-House Pilots records for 2012. 47 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 61 records from Liether Kalkgrube. 24 records from NABU-Fläche am Bösselhausener Weg. 17043 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 1 records from South American Antarctic Marine Biodiversity Literature. 4583 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 5772 records from Botany (UPS). 56 records from Dalbekschlucht. 44 records from Langes Tannen(LMS), Klasse 5d. 105 records from iHerbarium. 6 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 40956 records from Flora of the Stołowe Mts.. 126254 records from BioFokus. 31 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 1740 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Nectar. 1503 records from PonTaurus collection. 42 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 86 records from Steinbruch Mainz-Weisenau, 3. Jahr. 2 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 193 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 3 records from Goethe-Hauptschule/Projekt I-10. 35 records from Rechts des Inn Höhe Hofau Rosenheim. 5 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-747. 9342 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 31771 records from CIBIO, Alicante:ABH-GBIF. 611 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 27 records from Leben in den Elbwiesen. 7822 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 3 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7445 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 1 records from Herbario de Briófitos de la Universidad de Salamanca: SALA-Bryo. 6132 records from Catálogo para la utilización, conservación y disponibilidad de Phaseolus en México. 16 records from Pfrimmersbachtal. 263 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 5047 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 170 records from Gewann Krampf (Heilbronn). 8 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-748. 1271 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 1 records from MfN - Fossil vertebrates IV. 27142 records from Vascular plants of south-central China. 48 records from Alter Kreidebruch Saßnitz/Rügen. 230 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 7082 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 58 records from Schulgelände IGS Kaufungen. 131 records from Flora de los ecosistemas de la zona alta del río Coello. 6405 records from Composición florística y estructura de dos parcelas permanentes en bosques secos tropicales del municipio de Mendéz, Tolima. 1750 records from Flora of tanzania. 55618 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 19392 records from Central African Plants. 51 records from Weidewirtschaft. 5 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 2117 records from Jardín Botánico Atlántico, Gijón: JBAG. 215 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 54384 records from ALCB - Herbário Alexandre Leal Costa. 151 records from Bammentaler Duft- und Heilkräutergarten. 10 records from Monitoring of Nigritella nigra in the Kvikne mountains, Tynset, Norway. 51 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 214 records from Gwaii Haanas Marine Plants (OBIS Canada). 161 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 69 records from Draubiotop Lavamünd. 355655 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 12 records from Bachabschnitt der Nette (Osnabrück). 223945 records from Northern Ireland Environment Agency - EHS Species Datasets. 3839 records from Dataset of Global Change, altitudinal range shift and colonization of degraded habitats in mediterranean mountains (MIGRAME). 4 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 38 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 3912 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 40 records from Countryside Council for Wales - Shad Monitoring data. 587 records from Biosphärenpark Wienerwald - Pfaffstätten. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE258. 952 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 28 records from Biosphärenreservat Münsinger Alb. 254 records from Systematic census of the private plantations of the firewood of the Benin .. 17 records from Schafheide im Böblinger Wald. 18 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 1 records from Conocimiento de la macroflora marina de interés económico de las Costas de Yucatán. 45 records from Küste Wismar-Wendorf bis Hoben. 4 records from Tromsø Museum, Bryophytes. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 131 records from Stadtpark Herzberg (Elster). 23 records from Junge Heide, Radebeul/Dresden. 8 records from Riekdahler Wiesen. 1393 records from HAS - Herbário Alarich Rudolf Holger Schultz. 283 records from Clare Biological Records Centre dataset. 1 records from Schulgelände Kranich-Gymnasium (Salzgitter). 6306 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 41 records from Registros de hongos en áreas protegidas de la Argentina. 132351 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 3803 records from Manual de las gramíneas de Durango. 10 records from Programa de erradicación de los roedores introducidos en la Isla Rasa, Baja California: un plan de restructuración ecológica. 74 records from Luch Niederlehme, Schüler der Klasse 7. 180357 records from NMNH occurrence DwC-A. 27 records from verschiedene Kleingewässer um Oldenburg/Holstein. 9 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 1172 records from Plant Observation Records of Japan. 1 records from BIRDRACE Oostfreesland Bird-Lopers. 34 records from Naturpark Kottenforst-Ville 17.6.09. 1768 records from UFMT - Herbário UFMT. 1228 records from University of Amsterdam (NL) - Páramo pollen reference collection. 69 records from Schulgelände Paul-Gerhardt-Schule. 52 records from Schulwald Sprendlingen. 7131 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 49041 records from Institut Botanic de Barcelona, BC. 2857 records from Estonian Nature Observations Database. 23 records from Regenrückhaltebecken Bad Bevensen. 92 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 3736 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 165 records from Diversidad florística y estado de conservación en dos ventanas de paisaje de la UPR Tunjuelo priorizadas: Usme y Ciudad Bolivar, Bogotá. 1337 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 7497 records from La familia Asclepiadaceae en México. 41529 records from USU-UTC Specimen Database. 5 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 4 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE278. 196576 records from Instituto de Botánica Darwinion. 5 records from (Table 2) Median abundances of macrobenthos in surface sediments. 1112 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 66 records from Priest Pot species list, Cumbria, Britain. 9 records from Sandloch - Höhle. 1236 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 9443 records from Herbario de Universidad de Murcia: MUB. 2 records from Naturalis Biodiversity Center (NL) - Crustacea. 111 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 8839 records from National System of Protected Areas in Poland - Plants. 5053 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 41708 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 27090 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 1607 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 5764 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 50 records from Höltigbaum. 117 records from Schloss Fasanerie Eichenzell. 4 records from Bayerische Donau - Etterzhausen. 121 records from (Figure 8) Distribution of benthic foraminifers in the Pliocene-Quaternary of DSDP Hole 71-514. 10897 records from Census of species recorded during phytosociological surveys in Benin. 1 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1584830 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 98 records from Brander Wald (Stolberg). 34 records from Naturpark Kottenforst-Ville 18.6.09. 146582 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 75 records from Steinbruch Mainz-Weisenau. 402 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 4524 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 3437 records from MEXU/Leguminosae. 539 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 384 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 289 records from R-Tipos - Herbário do Museu Nacional - Tipos. 1025 records from tef-database. 291 records from nazza. 19 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 18 records from Schulhof Sandhofenschule (Mannheim). 1 records from HMAP-History pf Marine Animal Populations (CoML). 37 records from (Table 3) Benthic foraminiferal composition at DSDP Hole 84-565. 61 records from Registros restauración ecológica- Magdalena medio. 21 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 696263 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 623 records from Inventario de la biota terrestre (florístico) del parque nacional Isla Isabel. 52 records from NSG Leist bei Ziegenhain. 2650 records from Caracterización de la vegetación en los sectores de Aipe (Huila), Yaví (Tolima) y Dagua (Valle del Cauca), como insumo para la identificación de oportunidades de conservación y la recuperación de servicios ecosistémicos del bosque seco. 30 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 450 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 411 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 211 records from Pöhlberg bei Annaberg. 140 records from Naturpark Drömling. 1023 records from Geneva Herbarium – Boissier's Flora Orientalis (G-BOIS). 33 records from New records in vascular plants alien to Kyrgyzstan. 51656 records from New Mexico Biodiversity Collections Consortium database. 156003 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1496 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 115 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 1 records from Foraminifera abundance of Hole 55-430B. 6090 records from Herbario de la Universidad Industrial de Santander. 285 records from Schulzentrum "Parc Hosingen". 102 records from VFD-RP: Eifel: Orchideenweide Ankly. 17 records from Hemmerder Schelk (Unna). 929 records from Herbario HUAZ Enrique Forero. 110 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 93 records from Warnowtal (Rostock). 161 records from Schulhof Gymnasium Hürth Bonnstrasse. 3818 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 7 records from Paläontologie Marburg. 214061 records from Natural History Museum (London) Collection Specimens. 96 records from Marine species distributions in Irish coastal waters. 222 records from Danielsberg (Mölltal, Kärnten). 964 records from Perchtoldsdorfer Heide. 10 records from Neanderthal. 244 records from Schatzinsel Norderney. 218 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 850 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 7584 records from Herbarium togoense. 1110423 records from Vascular Plants, Field notes, Oslo (O). 2250 records from SLUI - Herbário Rosa Mochel. 6045 records from HERBAM - Herbário da Amazônia Meridional. 25 records from Feriendorf des Kreises Gedern (Ober-Seemen). 33626 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 950 records from Inventaire National du Patrimoine Naturel : CBN du Massif Central. 64 records from Gemeinschaftsgarten Deluxe (Bernburg). 2 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 77 records from Benthos counted on dredged samples during Valdivia cruise VA53. 23 records from Schulgarten Paul-Schneider-Schule, Münster. 33 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 7473 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 3427508 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 159 records from Regenrückhaltebecken (Zeulenroda). 109 records from Römertal (Steinpleis). 58 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 1 records from Lice (Phthiraptera) of Ireland. 3 records from Colección de Herbario. 79165 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 48 records from BTCV Scotland - BTCV wildlife counts recording workshops. 48 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 2018 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 12785 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 3 records from Birdrace-Die_Nachtraben-Stuttgart. 52 records from Naturerlebnisraum Koppelsberg (Plön). 4 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 2 records from BioMar (EurOBIS). 75 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 126604 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 75 records from VFD-RP: Taunus: Mähweide Dehe. 523 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 133029 records from Flora-On: occurrence data of the flora of mainland Portugal. 412 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Bosques. 13342 records from Paleobotany Division, Yale Peabody Museum. 11 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 482 records from Countryside Council for Wales - Freshwater Site Visits. 91 records from Coleoptera of Piska Forest. 28779 records from Herbier de Nouvelle-Calédonie. 160 records from Naturschutzgebiet Börstig bei Hallstadt. 515 records from Flora vascular del cerro El Zamorano. 2272 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 75217 records from Herbario Universidad de Antioquia (HUA). 532 records from Inventory of Bonou and Itchèdè forests in south east of Benin. 34 records from Coleoptera of Białowieża Forest. 99554 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 32 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 20174 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2 records from Grünfläche Forckenbeckplatz. 207 records from Triebesbach (Zeulenroda-Triebes). 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 165 records from Riedensee. 3219440 records from OEH Atlas of NSW Wildlife. 1 records from Wildnis Sturmschaden. 681 records from Ice and animal observations during POLARSTERN cruise ANT-X/6. 74 records from Artenvielfalt vor unserer Kita-Haustür. 1653 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 17 records from Levantamento de Herbáceas do PARNA Jaú. 1 records from Collection Polychaeta - ZIM Hamburg. 28 records from Schulgarten Zinnowwald-GS. 48 records from Ober-Olmer Wald 09. 434 records from Plant Specimens of Oiso Municipal Museum. 631 records from Wildlife Sightings. 46 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 44 records from Von der Nutzung zur Natur. 3 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 60 records from Waldwandel in Monschau-Mützenich-Boverei. 8063 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 17275 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 1558 records from The Flora of County Clare. 2639 records from Miscellaneous Vascular Plants. 46521 records from Vascular Plant Herbarium, UiB. 5 records from Schulinnenhöfe (Gelsenkirchen). 46 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 14333 records from Herbario Pontificia Universidad Javeriana. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 3793 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 32 records from (Table 13) Ranges of benthic foraminifers through the early to middle Miocene in ODP Hole 115-715A. 41006 records from Herbarium of Jyväskylä University Museum. 710 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 3694 records from Vascular plants of Amrum 2007-2008. 3527 records from Vascular plants in Danish coastal meadows. 1 records from BIRDRACE Gätkes Erben. 316 records from Freiburger Tag der Artenvielfalt. 538384 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 4 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 503 records from Inventario fitopatológico de las especies vegetales dominantes en la región de Zapotitlán de las Salinas, Pue.. 81 records from Langes Tannen. 2187 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 169 records from Knechtweide (Kohlfurth). 47 records from Ruhrwiesen bei Neheim-Hüsten. 5 records from Type Localities for organisms and fossils first described from Antarctica. 572 records from Thames Valley Environmental Records Centre - English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 21 records from Im Bauerngarten. 31 records from Issumer Fleuth. 12 records from Feuchtbiotop Otto-Hahn-Gymnasium. 461 records from GEO-Hauptveranstaltung (Duisburg). 214 records from University of Amsterdam (NL) - Páramo Vegetation Research, Paramo "El Almorzadero", Colombia. 871 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 48 records from VFD-H.: Rheingau: Bärstadt. 15878 records from Herbarium (AMNH). 666 records from Natural Geography In Shore Areas (NaGISA) Dataset. 121 records from NSG Haunestausee, Hauneteiche. 50 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 1710 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 60 records from Vorderer Tiergarten (Dessau). 36 records from Schwanseepark (87645 Schwangau). 57 records from Natural England - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 2465262 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 16 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 1573 records from Phragmites of Canada. 40 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 60103 records from Herbarium, Centre for Biodiversity, University of Turku, Finland (TUR). 162 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 249 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 2 records from Collection Ostracoda SMF. 5483 records from HURB - Herbário do Recôncavo da Bahia. 829589 records from PRECIS. 24 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 15 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 279 records from NODC WOD01 Plankton Database. 56 records from Artenvielfalt auf Restbauernhof. 78 records from VFD-H: Heidenrod: Pferdeweide Mürth. 207 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 22001 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 26186 records from Herbarium Senckenbergianum (FR). 10175 records from The DNA and Sample Repository at AIT. 293 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 6318 records from NINA botanical collection. 6 records from Birdrace-Usedommeln-Ostvorpommern. 143 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_1. 4 records from Field Museum of Natural History (Botany) Bryophyte Collection. 120660 records from OHN. 184 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 13 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 12916 records from Herbario de la Universidad de Almeria. 8086 records from SBT-Living. 459 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 4 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 670 records from Heritage Trees of Ireland. 32025 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 6585 records from HUEM - Herbário da Universidade Estadual de Maringá. 74 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 40 records from Bryophyte herbarium, Trondheim (TRH). 1 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2007. 26 records from Berlin - Treptower Park / Karpfenteich. 3399 records from Registros biológicos del género Piper en el herbario HUA. 2 records from Foraminifera abundance of Hole 48-403. 211 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 33 records from Saalewiesen Naumburg. 27 records from Streuobstwiese Haus Zeitz. 468 records from Bergkamen- Bergehalde Großes Holz. 156843 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 137 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 430 records from Rådgivende Biologer. 1 records from CUMV Bird Collection (Arctos). 2 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 980 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 107652 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 7545 records from FUEL - Herbário da Universidade Estadual de Londrina. 110 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 36 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 34 records from Listhof und Umgebung. 3109 records from Espèces vasculaires endémiques et orchidées (CITES). 1271410 records from Geographically tagged INSDC sequences. 90 records from Botanical Society of the British Isles - RISC Botanical Non-Native Species Records. 76 records from Ökologischer Weinberg (Guntersblum). 330 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 3 records from Ant'Phipoda Database (New records). 21685 records from Aranzadi Zientzi Elkartea. 82 records from Hamberger Brücke / Würmtal (Pforzheim). 3528 records from R - Herbário do Museu Nacional. 3161 records from Census in Agrimey forest reserve (southern Benin). 61 records from (Table 3) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-502A from the Caribbean Sea. 1292 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 32 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 413 records from Natural England - Invertebrate Site Register - England.. 8973811 records from Dutch Vegetation Database (LVD). 27032 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 9256 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010. 10512 records from MOSS - Herbário Dárdano de Andrade Lima. 340 records from Herbier G. Garapin (BOUM). 1351865 records from Consortium of California Herbaria. 604 records from HUSC - Herbário Unisanta. 148 records from Isarufer. 6 records from Merseyside BioBank - North Merseyside Insects (unverified). 4 records from French Grapevine Genetic Resources Center. 295 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 232 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 25 records from FFH-Gebiet Paartal. 241 records from Tag der Artenvielfalt. 143972 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 3948 records from tan-database. 6 records from Kindergarten. 19 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 50 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 184 records from FFH-Gebiet Ahrbachtal. 95 records from NSG Berschau - Auengebiet (Neustadt / Wied). 341340 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 942 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 696 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 218 records from Butterberg, Dardesheim. 15 records from Breitkopfbecken (Berlin-Reinickendorf). 52 records from Erzental (Oberotterbach). 28531 records from Online Atlas of vascular plants 2012-2020. 2 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 48 records from Kinderbauernhof Pinke-Panke. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 20535 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2360 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 485 records from Artenvielfalt am Schlern. 1354 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 38998 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 5 records from Fongs d'Andorra. 1 records from Sächsische Schweiz (Wehlener Gebiet). 7 records from Diveboard - Scuba diving citizen science observations. 3911 records from Colección de Monocotiledóneas Mexicanas (UAM-I). 746 records from Flora acuática de Querétaro. 13 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 14 records from Mycological Collection - University of Washington Herbarium (WTU). 444 records from Biodiverisity Group, Dept. of Environment, Food and Agriculture,Isle of Man Government - Japanese Knotweed Records in the Isle of Man 1991-2008. 14969 records from Environment Agency - Environment Agency Non-native Species records v1. 1551 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 37039 records from Herbarium (ICEL). 633 records from GEO Hauptveranstaltung Tirol (Innsbruck). 283 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 44 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 16746 records from BioGIS - Vascular plants - HUJ Herbarium. 3 records from FFR Hausen. 1717 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 2904 records from Botanical Museum, Denmark. Database of registrations of red listed plants. 7 records from Foraminifera abundance of Hole 57-438. 106 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 796 records from Flora de las Barrancas del Cobre. 1942 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Pereira, Risaralda. 745 records from UCBG TAPIR Provider. 79 records from IG TUT paleontology. 159 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 73561 records from Herbarium Willing. 26 records from NSG Dellwiger Wald, Dortmund. 2700 records from Herbarium - Las Cruces Biological Station. 10 records from Feuchtwiesen Wippertal bei Wippra. 102 records from Oberes Schindelbachtal. 1 records from Real Jardin Botanico, Madrid: MA-Algae. 19419 records from HVASF - Herbário Vale do São Francisco. 256 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 42 records from Die Wuhle. 17 records from Salzwiese Diekskiel. 59 records from Nationalpark Jasmund. 1 records from Haselbachtal. 13 records from Edaphobase. 68 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 206 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007.
Keywords: GBIF; biodiversity; species occurrences